Pesan Moral dan Relevansi Kitab Ester bagi Kehidupan Modern - Yunita Ester Fay; Sinta Peni; Malik Bambangan (Jurnal Filsafat dan Teologi Katolik, 2025)
The Book of Esther delivers a powerful moral message about courage, wisdom, and faith amidst the threat of genocide against the Jewish people. Although the name of God is not explicitly mentioned, the book reveals God’s providence working behind the scenes through the character of Esther. By placing her as queen, God used her bravery and resolve to save His people from destruction. This article explores the moral messages in the story of Esther and their relevance in modern life, especially regarding female leadership, faithful obedience, and the courage to face challenges. The research employs a qualitative method through literature analysis. Findings show that values in the Book of Esther—such as trust in God, prayer, integrity, and self-sacrifice—remain relevant as moral and spiritual inspiration in contemporary life.